Working With an Unusually Structured Text, Dialogue, Or Monologue in English (Open Academia: Journal of Scholarly Research, 2023)
In this article, working with an unusually structured text, dialogue or monologue in English, paying attention to the development of students' speech and speaking skills in each lesson on grammatical understanding , teaching foreign languages in a local school information about the renewal processes in the field.